Building brand loyalty: An application of expectation confirmation model in mobile social commerce - Wajeeha Aslam; Marija Ham; Kashif Farhat (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The study seeks to examine the role of perceived usefulness (PU) and confirmation (CN) on continuance usage intention of mobile social commerce (CI) and on user satisfaction (S). Furthermore, it examines the role of continuance intention and user satisfaction on brand loyalty (BL). Also, this study seeks to examine the role of gender and online shopping experience. This study also validates the model that combines brand loyalty and expectation confirmation model (ECM) in the mobile social commerce context. For this, the data was collected from a sample of 344 respondents from Pakistan and structural equation modeling(SEM) was applied using Amos 22. Results of the study reveal that PU is influenced by CN whereas CN does not have an impact on S. Furthermore,PU established a significant impact on S and CI, but S does not assure CI. Likewise, S and CI both have an impact on BL. The study also found differences in consumer behavior based on gender and online shopping experience. This study is helpful to the social commerce companies as it identifies the key elements that boost brand loyalty. Hence, this study recommends numerous managerial implications
Keywords: 330; mobile social commerce; brand loyalty; user satisfaction; continuance intention; online shopping experience; expectation confirmation model